Habitat availability is not limiting the distribution of the Bohemian–Bavarian lynx Lynx lynx population. Issue 4 (6th August 2015) - Magg, Nora; Müller, Jörg; Heibl, Christoph; Hackländer, Klaus; Wölfl, Sybille; Wölfl, Manfred; Bufka, Ludêk; Červený, Jaroslav; Heurich, Marco
Abstract: A population of Eurasian lynx Lynx lynx was established by reintroductions in the Bohemian Forest Ecosystem in the 1970s and 1980s. The most recent information on the population status indicates that the distribution has stagnated since the late 1990s, for unknown reasons. We assessed the availability of suitable habitat along the Austrian–German–Czech border, and hypothesized that the Bohemian–Bavarian lynx population is not in equilibrium with habitat suitability. Based on global positioning system data from 10 radio-collared lynx, we used a maximum entropy approach to model suitable habitat. Variables reflecting anthropogenic influence contributed most to the model and were negatively associated with the occurrence of lynx. We evaluated the model prediction using independent records of lynx from monitoring in Bavaria, Germany. Using our habitat approach we estimated the area of potential habitat, based on a mean annual home range of 445 km 2 for males and 122 km 2 for females. Our results indicated there were 12, 415 km 2 of suitable habitat, distributed among 13 patches, for a potential population of c. 142 (93–160) resident lynx. We assessed connectivity via least-cost paths and found that all suitable patches could be reached by the lynx. A comparison with the current distribution of lynx, however, confirms that a significant proportion of suitable habitat is not occupied, which indicates that the distribution is limited by factors other than habitat, with illegal killing being the most likely cause. Our study provides crucial information for the development of a conservation strategy and regional planning for the Bohemian–Bavarian lynx population.